STUDY OF LIQUID SURFACE CHANGES IN A MOVING CONTAINER USING THE SMOOTHED PARTICLE HYDRODYNAMICS METHOD - Wahyu Utami, Amalia
Fluid transport using moving containers requires knowledge of the effects of container motion on the liquid surface. This issue is commonly encountered in energy and process industries that involve fluid transfer using trucks or ships, and clinical laboratories utilizing robots for sample analysis in worst-case scenarios, the liquid can spill and cause damage, leading to various losses. Numerical modelling to study this phenomenon is conducted by modifying the MATLAB code of the SPHM package for the case of fluid motion due to shear force in a closed container with a base size 1 mm, a height of 1 mm, and a total of 1600 fluid particles. The SPHM package will be adapted for the case of an open container, incompressible fluids, and the XSPH Monaghan variant, with body forces applied in this study’s simulation. The numerical modelling simulations will be executed on a computer powered by a 13th Gen Intel (R) Core (TM) i9-13900K processor. Parameters adjusted in the simulations include pressure parameter times the sound speed in Morris’s artificial water pressure equation, the number of fluid particles through changes in particle rows, and the container velocity. At the initial condition of the fluid surface, the effects of varying pressure parameter on the distance between fluid particles and the container wall, as well as the effect of particle count on the steady-state liquid height, will be observed. During container motion, the effect of container velocity on the number of the particles remaining in the container after movement will be examined. The results indicate that adjusting pressure parameter in variations of 1-40 particle rows successfully prevents fluid particles from being too close to the container walls, with the closest particle-wall distance ranging between 0,022 mm and 0,039 mm, or 1,8-3,1 time the Lennard-Jones potential cutoff distance. Additionally, the final steady-state liquid height is directly proportional to the number of particle rows, with a Pearson correlation coefficient of r=0,99. Lastly, the faster the container moves, the more particles spill from the container, as observed for container velocities of 0,18 m/s, 0,15 m/s, 0,1 m/s, and 0,05 m/s, with the respective particle spill percentages being 7,4%, 4,1%, 3,5%, and 0,42% of the initial 960 fluid particles. Keywords: SPH, water simulation, water spillage phenomenon, moving container